PROSES PENEGAKAN HUKUM TERHADAP ANGGOTA POLRI YANG MELAKUKAN PELANGGARAN DISIPLIN KEPOLISIAN - Narto S.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
The variety of police duties in the modern era police position as law enforcement agents who have high interaction with the community, particularly the police interaction with different types of crime in the community so as to make the police activity as an activity that puts its members in so many occasions to the contrary. Law enforcement process discipline members of the police are still found any rule of law that overlap, yet found any members of the police who are in the process of checking the Police Internal Affairs investigators, mutated by other units. Constraints in law enforcement process against members of the police who violate the Police Discipline in Magelang City Police are calling for the examination of witnesses in the members of the police are often not timely by reason of service. Factors contributing to the violation disiplin kepolisian in Magelang City Police is less understanding of the law, the type of arrogant personality, faith and devotion less members of the police, domestic issues and economic burden, rampant nightlife venues in Magelang Police Region city of potentially visited by members of the police investigating the reasons are not equipped Task Order.